A putative ABC transporter gene, CcT1, is involved in beauvericin synthesis, conidiation, and oxidative stress resistance in Cordyceps chanhua - Zhimin Liu; Jiahua Zhu; Ruixue Gong; Zhiyuan Wen; Yanwen Liu; Yulong Wang; Zengzhi Li; Bo Huang; Fan Peng (Microbiology Spectrum, 2025)
ABSTRACT Cordyceps chanhua is a traditional Chinese medicinal fungus renowned for producing a variety of bioactive compounds, including beauvericin (BEA). BEA has garnered significant attention due to its therapeutic potential and associated food safety concerns. In this study, we identified an ATP-binding cassette (ABC) transporter-encoding gene, CcT1, located within the BEA synthesis gene cluster of C. chanhua. Disruption of CcT1 resulted in a substantial decrease in BEA production. RT-qPCR analysis demonstrated that the loss of CcT1 significantly downregulated the expression of several BEA synthesis-related genes, including pyruvate kinase, branched-chain amino acid aminotransferase, and ketoisovalerate reductase. Beyond its role in BEA biosynthesis, CcT1 was found to influence hyphal growth, conidiation, conidial germination, and the oxidative stress response in C. chanhua. Additionally, the CcT1 knockout strain exhibited a reduced ability to penetrate host cuticles, highlighting the gene’s role in fungal pathogenicity. These findings offer a comprehensive understanding of the multifaceted roles of the ABC transporter CcT1 in hyphal development, conidiation, BEA biosynthesis, and stress resistance in C. chanhua. Moreover, targeting CcT1 presents a promising strategy for reducing BEA content through molecular breeding, thereby enhancing the safety and efficacy of C. chanhua as a medicinal agent.IMPORTANCEBeauvericin (BEA) is one of the bioactive components in Cordyceps chanhua, a significant medicinal fungus with widespread use in Asia and beyond. BEA also possesses mycotoxin properties, with certain cytotoxicity and potential in vivo toxicity. However, few studies report the regulation of BEA anabolism. ABC transporters are a superfamily of membrane proteins and have multiple functions such as regulating fungal metabolism. Here, we report an ABC transporter CcT1 involved in BEA synthesis. The disruption of its encoding gene CcT1 led to a 64.22% reduction in BEA content compared to the wild-type by regulating the expression levels of several BEA synthesis-related genes. It also affected hyphal growth, conidiation, spore germination, penetration, and oxidative stress resistance of the fungus. The findings in this study enrich the understanding of the function of ABC transporter in fungal metabolism and growth and development.